Perbandingan Gelombang Longitudinal dan Transversal: Eksperimen pada Media Berbeda - Isti Hidayah; Devi Amanda; Nurul Hasanah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Waves are vibrations of energy that move through something or without something. Depending on what they pass through, waves are divided into two groups, namely transverse waves and longitudinal waves. This study uses an experimental method, which means based on experimental research. Data were collected by observing and recording what happened. The study was conducted at STKIP Al Maksum Langkat. Longitudinal waves on a slinky, the direction of vibration is in the form of particles on the slinky vibrating in the direction of wave propagation. The longitudinal wave pattern forms a pattern of compression and stretching on the slinky. The wave speed on the longitudinal on the slinky is influenced by the elasticity and density of the slinky. Transverse waves on a rope, the direction of vibration is in the form of particles [on the rope vibrating perpendicular to the direction of wave propagation. The transverse wave pattern forms a pattern of hills and valleys on the rope. The speed of transverse waves on the rope is influenced by the elasticity and density of the rope.